Potential ascertainment of underground water resources in Ica region - Sebastián Calvo, Carlos (2018)
The Ica-Peru region has great agro-export potential in the country. It is a privileged region for this type of investment because of its quality of soil, climate, hours of sunshine and luminosity, which makes it very competitive; achieving high levels of productivity and quality in their crops. Employment in Ica grew at a level of 31% per month during the harvest periods dedicated to agricultural exports, achieving full employment, which has allowed its population to access higher levels of living and consumption. The overexploitation of aquifers in the project area has been identified as the central problem evidenced by the continuous descent of groundwater levels, a fact that is affecting groundwater reserves, and in some cases, the quality of them. In addition, the irrational and deficient use of groundwater has as indirect causes the informality in the exploitation of the aquifer.